LRRK2 impairs autophagy by mediating phosphorylation of leucyl‐tRNA synthetase. (8th November 2018) - Ho, Dong Hwan; Kim, Hyejung; Nam, Daleum; Sim, Hyuna; Kim, Janghwan; Kim, Hyung Gun; Son, Ilhong; Seol, Wongi
Abstract : Leucine‐rich repeat kinase 2 (LRRK2) is a causal gene of Parkinson disease. G2019S pathogenic mutation increases its kinase activity. LRRK2 regulates various phenotypes including autophagy, neurite outgrowth, and vesicle trafficking. Leucyl‐tRNA synthetase (LRS) attaches leucine to tRNA Leu and activates mTORC1. Down‐regulation of LRS induces autophagy. We investigated the relationship between LRRK2 and LRS in regulating autophagy and observed interaction between endogenous LRRK2 and LRS proteins and LRS phosphorylation by LRRK2. Mutation studies implicated that T293 in the LRS editing domain was a putative phosphorylation site. Phospho‐Thr in LRS was increased in cells overexpressing G2019S and dopaminergic neurons differentiated from induced pluripotent stem (iPS) cells of a G2019S carrier. It was decreased by treatment with an LRRK2 kinase inhibitor (GSK2578215A). Phosphomimetic T293D displayed lower leucine bindings than wild type (WT), suggesting its defective editing function. Cellular expression of T293D increased expression of GRP78/BiP, LC3B‐II, and p62 proteins and number of LC3 puncta. Increase of GRP78 and phosphorylated LRS was diminished by treatment with GSK2578215A. Levels of LC3B, GRP78/BiP, p62, and α‐synuclein proteins were also increased in G2019S transgenic (TG) mice. These data suggest that LRRK2‐mediated LRS phosphorylation impairs autophagy by increasing protein misfolding and endoplasmic reticulum stress mediated by LRS editing defect. Significance of the study: Leucine‐rich repeat kinase 2 (LRRK2) is the most common genetic cause of Parkinson disease (PD), and the most prevalent pathogenic mutation, G2019S, increases its kinase activity. In this study, we elucidated that leucyl‐tRNA synthetase (LRS) was an LRRK2 kinase substrate and identified T293 as an LRRK2 phosphorylation site. LRRK2‐meidated LRS phosphorylation or G2019S can lead to impairment of LRS editing, increased ER stress, and accumulation of autophagy markers. These results demonstrate that LRRK2 kinase activity can facilitate accumulation of misfolded protein, suggesting that LRRK2 kinase might be a potential PD therapeutic target along with previous studies.